2016
DOI: 10.1186/s12893-016-0197-3
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial on effects of different hemostatic sponges in posterior spinal fusion surgeries

Abstract: BackgroundSpinal fusion surgery is associated with significant blood loss, which may result in potential clinical complications, it is necessary to take safe and effective measures to reduce blood loss in surgery. We perform this study to assess the impact of three different hemostatic materials on perioperative blood loss.MethodsWe performed a Randomized Controlled Trial research and recruited patients with lumbar disease into the study between November 2013 and March 2015. All the participants were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The use of collagen-based and gelatin-based products has led to a significant reduction in both intraoperative blood loss and postoperative transfusions. The effectiveness of these two types of products has been compared in a recent randomized controlled trial performed by Xu et al [ 40 ] on 92 patients who had undergone spinal fusion surgery. The authors concluded that collagen-based products demonstrated better hemostatic effect than gelatin-based products, with lower blood loss and postoperative drainage volume.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of collagen-based and gelatin-based products has led to a significant reduction in both intraoperative blood loss and postoperative transfusions. The effectiveness of these two types of products has been compared in a recent randomized controlled trial performed by Xu et al [ 40 ] on 92 patients who had undergone spinal fusion surgery. The authors concluded that collagen-based products demonstrated better hemostatic effect than gelatin-based products, with lower blood loss and postoperative drainage volume.…”
Section: Resultsmentioning
confidence: 99%
“…True sealants (“cross-linking”) can be divided into synthetic (PEG-polyethylene glycol-based and cyanoacrylate) [ 40 46 ] and semi-synthetic (glutaraldheide-albumin) [ 49 ]. In contrast to fibrin glue, cross-linking sealants polymerize through a non-enzymatic chemical reaction, which do not require the presence of blood or any components of the coagulation cascade.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that the hematocrit (Hct) of postoperative drainage may fluctuate over a wide range; therefore, the use of only the amount of drainage as the reference for postoperative blood loss is inaccurate. [ 10 ] In our study, we also examined the complete blood count (CBC) for every drainage sample to obtain Hct and hemoglobin (Hb) data, which were used to calculate the pure blood contained in the drainage.…”
Section: Methodsmentioning
confidence: 99%
“…Most of previous studies treated volume of drainage as postoperative blood loss; however, the volume of drainage is not equal to the postoperative blood loss according to the Gross formula. Because the component of drainage varied with time varying, so postoperative blood loss does not depend on the amount of fluid loss but the pure blood contained in drainage [ 11 , 12 ]. In our study, we also examined complete blood count (CBC) for every drainage sample to obtain data of HCT and hemoglobin (HGB), which were used to calculate the precise blood contained in drainage.…”
Section: Resultsmentioning
confidence: 99%